Effectiveness of online learning during pandemic of Covid-19 among educators in higher learning institutions: an overview / Noor Hidayah, Mohd Farizi and Dazmin Daud - Azhar, Noor Hidayah; Jamaluddin, Mohd Farizi; Daud, Dazmin (Centre For Media And Information Warfare Studies, 2021)
The rise of pandemic Covid-19 worldwide has change the way we conduct things. Educators are among the group that impacted from this pandemic. The effectiveness of online lecture conducted among educators in Higher Learning Institutions has been questioned by stakeholders such as students, parents including the institutions it selves. Hence, the present study reviewed on the factors contributed towards the effectiveness and the mitigation strategies to be adopted by educators in facing challenges of conducting lectures, exams, consultations, and assessment via online. Various factors shall be considered in achieving the effective online learning in Higher Learning Institution. The announcement made by the government on MCO 3.0 recently has raised more concern among the stakeholders on the changes of virtual education. Due to this, the relevant tools in mitigating the problem and good assistance from various parties could give a positive enhancement towards online learning further discussed. Systematic review was conducted in collecting information relating to factors contribute towards effective teaching and ways to overcome its challenges gathered and further analyzed. This overview provides higher learning institutions with a check-list kit to conduct an audit for measuring their teaching and learning effectiveness during a crisis.